The Merchant of Venice - Shakespeare, William; West, Clare; Girard, Thomas (Oxford :Oxford University Press, 2016)
In sixteenth-century Venice - a city of wealthy merchants and bankers - money is all-important. Bassanio is penniless, but his great friend Antonio offers to help him by borrowing the money that he needs. To do this, though, Antonio must make an arrangement with an old enemy that puts his life in danger... The Merchant of Venice is one of Shakespeare's most popular plays, and it has been performed all over the world. It is retold in this Bookworm not as a play, but as a story.
Stage 5
Keywords: Lengua inglesa -- Lecturas